2016
DOI: 10.1017/s0033291716002166
|View full text |Cite
|
Sign up to set email alerts
|

A study of wrist-worn activity measurement as a potential real-world biomarker for late-life depression

Abstract: BackgroundLate-life depression (LLD) is associated with a decline in physical activity. Typically this is assessed by self-report questionnaires and, more recently, with actigraphy. We sought to explore the utility of a bespoke activity monitor to characterize activity profiles in LLD more precisely.MethodThe activity monitor was worn for 7 days by 29 adults with LLD and 30 healthy controls. Subjects underwent neuropsychological assessment and quality of life (QoL) (36-item Short-Form Health Survey) and activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 35 publications
6
40
0
2
Order By: Relevance
“…The motor cortex and cerebellum are regarded as important brain regions related to voluntary movement and motor control (44,45). Deficits in motorrelated functions have recently been observed in LLD patients (46). Thus, our observation of decreased DC in somatosensorymotor cortices and altered cerebellar DC in the LLD patients might be related to the somatosensory abnormalities and motor deficits associated with depression.…”
Section: Discussionsupporting
confidence: 51%
“…The motor cortex and cerebellum are regarded as important brain regions related to voluntary movement and motor control (44,45). Deficits in motorrelated functions have recently been observed in LLD patients (46). Thus, our observation of decreased DC in somatosensorymotor cortices and altered cerebellar DC in the LLD patients might be related to the somatosensory abnormalities and motor deficits associated with depression.…”
Section: Discussionsupporting
confidence: 51%
“…In support of Aim 1, MPI Walther showed that overall gross motor activity, as measured by wrist actigraphy, is reduced in acutely depressed individuals [27,55] and stable over 1 week [56]. This replicates other studies of MDD across the lifespan (youth, late life) [57][58][59][60]. As a preliminary test of whether this deficit continues into remission, MPI Walther examined actigraphy levels of 22 MDD patients during treatment.…”
Section: Actigraphy In Depressionsupporting
confidence: 59%
“…Our methods of automatic analysis allowed speech to be objectively detected while maintaining the privacy of participants. We previously reported a high level of compliance with the device protocol (92% for each group; O'Brien et al, 2017).…”
Section: Analysis Of Speech Datamentioning
confidence: 97%